Paradoxes of expert approaches to the study of cultural infrastructure: The Ukrainian case - Svitlana Ovcharenko (CES Working Papers, 2020)
The article reveals the imperfection of ways to use existing approaches to the study of the cultural infrastructure in Ukraine, in particular when we apply methods offered by the UN and the EU as well. The research evidences that both foreign and Ukrainian experts are taking the first steps to ascertain the condition of cultural infrastructure in Ukraine and currently there is no objective complete database. Positive characteristics of different ways of measuring the state of cultural infrastructure are proposed to unite and Ukraine should be considered as the base country for testing scientific research methods, which will facilitate the establishment of scientific cooperation in the field of cultural policy and the coordination of joint decisions for cross-border partnership. One of the additional important parameters for the study of cultural infrastructure is its relevance to the overall political plans for the development of culture in the European community.
Keywords: 330; cultural infrastructure; cultural resources; cultural policy